1961
DOI: 10.1084/jem.113.3.485
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Arthritis and Other Lesions Induced in Rats by Injection of Mycobacterial Adjuvant

Abstract: A generalized disease is induced experimentally in the rat by administration of Freund's adjuvant. The primary clinical and pathologic lesions are arthritis, periarthritis, peritendinitis, and periostitis in the joints of the extremities and tail. Accompanying the arthritis in some cases, and never observed in its absence, are other specific tissue lesions including iridocyclitis, nodular lesions in the glabrous skin (ear, genitalia, feet, tail), transient rashes, a chronic skin disease, genitourinary lesions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
101
0
2

Year Published

1965
1965
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(113 citation statements)
references
References 37 publications
10
101
0
2
Order By: Relevance
“…Some of the reports described the usefulness of adjuvantpolyarthritis for testing of drugs for antiinflammatory activity, because the pathogenicity of adjuvant-arthritis in rats resembled certain human rheumatoid syndromes [11,13,17].On the mechanism of adjuvant-polyarthritis, it has been reported that the delayed type hypersensitivity of the tubercle bacilli was involved [9,16]. Wood et al [20] and Jolles and his co-workers [7,8] had shown relationships between the chemical structure and arthritogenicity of mycobacterial wax D and cell walls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the reports described the usefulness of adjuvantpolyarthritis for testing of drugs for antiinflammatory activity, because the pathogenicity of adjuvant-arthritis in rats resembled certain human rheumatoid syndromes [11,13,17].On the mechanism of adjuvant-polyarthritis, it has been reported that the delayed type hypersensitivity of the tubercle bacilli was involved [9,16]. Wood et al [20] and Jolles and his co-workers [7,8] had shown relationships between the chemical structure and arthritogenicity of mycobacterial wax D and cell walls.…”
mentioning
confidence: 99%
“…Some of the reports described the usefulness of adjuvantpolyarthritis for testing of drugs for antiinflammatory activity, because the pathogenicity of adjuvant-arthritis in rats resembled certain human rheumatoid syndromes [11,13,17].…”
mentioning
confidence: 99%
“…This disease resembles rheumatoid arthritis (RA) and Reiter's syndrome in a number of clinical and pathologic characteristics (5)(6)(7)(8)(9). Several experiments have been conducted on the antiinflammatory action of DMSO in adjuvant arthritis in rats.…”
Section: Penetration and Effect Of Topically Applied Dimethylsulfoxidmentioning
confidence: 99%
“…AIA, which appeared in rats immunized with Mycobacterium tuberculosis in oil, showed suggestive similarities in clinical onset and course, as well as the pattern of lesions in joints, skin, eye, and mucosae, to reactive arthritis associated with infection by enteric organisms (primarily gram-negative bacilli) (for review, see ref. 5). The intensified, precocious appearance of AIA lesions at joint or skin sites traumatized by various means suggested that the disease might represent a disseminated autoimmune response to a joint or connective tissue antigen (6).…”
Section: Introductionmentioning
confidence: 99%